Sodium Nitrate Improves Oxidative Energy Contribution and Reduces Phosphocreatine Contribution During High-Intensity Intermittent Exercise - Sacramento, Henrique Silva; da Silva, Lucas Chalegre; Papoti, Marcelo; Rossi, Fabrício Eduardo [UNESP]; dos Santos Gomes, Willemax; dos Santos Costa, André; Campos, Eduardo Zapaterra (Taylor & Francis, 2024)
The present study aimed to verify the effect of acute nitrate supplementation on oxidative, phosphocreatine, and glycolytic energy contribution (COXI, CPCr, and CLAC, respectively) during a high-intensity intermittent exercise (HIIE). Fifteen physically active subjects were submitted to incremental running test on a treadmill and two random HIIE (10 × 1 min at maximal aerobic speed with 1 min of passive recovery) in the following conditions: sodium nitrate (SN) or Placebo (PL). Repeated measure ANOVA was used to compare COXI, and CPCr within the 10 efforts. Student t test was used to compare total COXI, CPCr, CLAC, as well oxidative and non-oxidative contribution. Considering the 10 efforts, COXI presented the main effect for condition (F = 16.7; p =.001; SN: 1.9 ± 0.1 L; PL: 1.6 ± 0.1 L), and no interaction effect (F = 0.9; p =.415), while CPCr presented effect for condition (F = 13.4; p =.003; SN: 1.2 ± 0.1; PL: 1.4 ± 0.8 L), and no interaction (F = 1.2; p =.317). Total oxidative contribution were higher (p <.001) after SN (19.1 ± 3.4 L) than Placebo (16.7 ± 3.1 L), while total CPCr were lower (p =.002) after SN (12.4 ± 2.5 L) than PL (14.1 ± 2.6 L). Total energy contribution were not different between trials. Acute dose of SN supplementation improved oxidative contribution during HIIE, and reduced CPCr. Higher COXI is likely related to increased oxygen kinetics, while the lower CPCr might be related to the improved energetic efficiency.
Keywords: Energy system contribution; high-intensity intermittent training; nitrate supplementation